Patching and Suppression in Amblyopia: One Mechanism or Two? - Chen, Yiya; He, Zhifen; Mao, Yu; Chen, Hao; Zhou, Jiawei; Hess, Robert F. (Frontiers in Neuroscience, 2020)
Purpose: To determine if benefits from occlusion therapy are due to decreased suppression from the fellow eye in children with amblyopia. Methods: Ten newly diagnosed amblyopes (7.2 ± 1.4 years old), two with strabismus and eight with anisometropia, participated. Patients were first given a 2-month period of refractive adaptation, followed by occlusion therapy (i.e., patching their fellow eye with an opaque patch for 4 hours/day). Visual acuity of the amblyopic eye and interocular suppression were measured before and after 0.5, 1, 2, 4 and 6 months of occlusion therapy. We quantified interocular suppression with a binocular phase combination task. Results: Visual acuity (in logMAR) improved from 0.50 ± 0.22 (mean ± SD) to 0.33 ± 0.20 for patients who finished a short-term (two months) occlusion (A1 to A10), from 0.53 ± 0.20 to 0.32 ± 0.22 for patients who finished a medium-term (four months) occlusion (A1 to A9) and from 0.48 ± 0.19 to 0.22 ± 0.10 for patients who finished a long-term (six months) occlusion (A1 to A8). Although their visual acuity significantly improved, their degree of suppression, which was abnormal in all cases, did not change consistently. This was true in all durations of occlusion therapy. Conclusions: Reduced suppression from the fixing eye might not be result from occlusion therapy.